Lithological and geochemical characterization of ‘adinole’ artefacts from cave deposits in southwest Wales: A material of choice during the late Middle to Upper Palaeolithic - Richard Bevins; Elizabeth A. Walker; Nick Pearce; Duncan Pirrie; Rob Ixer; Ian Saunders; Matthew Power (Quaternary Environments and Humans)
Twenty-three artefacts previously identified as being manufactured from adinole, a fine-grained metasomatic rock, from late Middle to Upper Palaeolithic cave sites in southwest Wales have been re-examined in terms of their petrology and geochemistry. Standard petrography has been combined with automated SEM-EDS analysis for a single artefact to determine the mineralogy and textures of that artefact, while portable XRF and μXRF have been combined to establish the geochemical characteristics of all twenty-three artefacts analysed. These investigations have shown that the artefacts were manufactured from rhyolite rather than adinole, a misidentification that has been in the literature for over 100 years. Some artefacts appear to cluster on geochemical plots, such as a group of eight artefacts from Hoyle’s Mouth Cave which share petrological characteristics and appear to have come from a common source. In other cases, however, certain artefacts with similar chemistries have dissimilar petrological characteristics and are not from a common source. This highlights the need to consider both petrological and geochemical characteristics when classifying rhyolitic artefacts. The artefacts studied show that this spotted variety of rhyolite was a preferred source of raw material throughout the late Middle and Upper Palaeolithic, despite having no obvious physical or practical advantages. Identifying rhyolite rather than adinole as the raw material used in the manufacture of the studied artefacts negates the need to consider long distance transport of either raw materials or finished artefacts. It strongly suggests that people in southwest Wales, where raw materials were scarce, were using materials that were local to them. Further, there is evidence that people were effectively planning for future use or reuse of artefacts, involving curation of tools. The next phase of work will use the lithological characteristics identified here to explore potential sources for the raw material used in the manufacture of these artefacts.